Dinapenia, baixo índice de massa muscular esquelética apendicular ou sarcopenia de acordo com o EWGSOP2: Qual o melhor indicador de risco para o declínio da velocidade de caminhada em homens e mulheres? - Souza, Isabella Letícia de Pádua Cruz e (2023)
Mobility, measured by walking speed (WS), is considered the sixth vital sign in the assessment of the elderly. Its limitation compromises independence and increases the risk of falls, functional loss, hospitalization and death. Despite sarcopenia and dynapenia being two important risk factors for mobility decline, the search for cutoff points capable of predicting such decline early remains a challenge in clinical practice. Thus, the present dissertation aimed to compare dynapenia, with low appendicular skeletal muscle mass index (ASMMI) and with sarcopenia, defined by the consensus of the European Working Group on Sarcopenia in Older People 2 (EWGSOP2), in order to verify what would be the best indicator to determine the risk of WS decline in men and women. A longitudinal study was conducted with 2,680 individuals aged 60 years or older free of mobility limitations (WS > 0.8 m/s) who participated in the English Longitudinal Study of Aging (ELSA). Dynapenia was defined by handgrip strength (HGS) (< 39, < 36, < 32, < 30, < 27 and < 26 kg for men and < 23, < 22, < 21, < 20, < 17 and < 16 kg for women). Low ASMMI was defined by the 20th percentile of the sample distribution of appendicular skeletal muscle mass/height2 (< 9.24 kg/m2 for men and < 6.52 kg/m2 for women) and sarcopenia was defined by the EWGSOP2 consensus using the different grades for HGS. Generalized linear mixed models controlled for socioeconomic, behavioral and clinical factors were used to analyze the decline in WS (m/s) as a function of dynapenic status, low ASMMI and sarcopenia, separately, during an eight-year follow-up period. Over time, women with dynapenia < 17 kg (- 0.005 m/s per year; 95%CI: - 0.01 – - 0.001) and < 20 kg (- 0.007 m/s per year; 95%CI: - 0.01 – - 0.001) when compared to those without dynapenia ≥ 17 and ≥ 20 kg, respectively. In clinical terms, this means an eight-year decline of -0.14 m/s in the HGS < 17 kg group and a decline of -0.15 m/s in those with HGS < 20 kg. As for sarcopenia, the greatest decline in WS occurred only in women with probable sarcopenia [(- 0.006 m/s per year; 95%CI: - 0.01 – - 0.001, HGS <17 kg) and (- 0.007 m/s per year year; 95%CI: - 0.01 – - 0.001, HGS <20 kg)]. In clinical terms, this means an eight-year decline of -0.15 m/s for both cutoff scores. Dynapenia, low ASMMI and sarcopenia for men and low ASMMI and sarcopenia for women were not able to identify the risk of mobility decline. Women aged 60 years or older and free from mobility limitations, when they have dynapenia and probable sarcopenia, defined by HGS < 17 kg and < 20 kg, are at greater risk of mobility decline over time and should be targeted for early interventions to that this condition is not met.